Pareto Analysis on National Issues in Textile Industry in Pakistan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
This research investigates the Pareto Analysis on National Issues in Textile Industry in Pakistan. Data were collected from Primary as well as secondary sources It is a statistical research technique in decision making that is used for the selection of a limited number of tasks that produce significant overall effect. It separates the few major problems from the many possible problems. It is named after Vilfredo Pareto, a 19th-century Italian economist. It was revealed that Textile spinning sector detail of analysis performed for reducing a huge number of issues explored from textile industry of Pakistan in the era of trade liberalization. It was revealed that high cost of production, industrialists are highly risk averse, lack of training programs, R&D facility of 6% has been withdrawn, no collective method for solving the industrial problems, changing name from EPB to TDAP is not the solution, textile / garments city project can be a powerful tool, industrialist shifting business to other countries , lack of funds, labors shifting to other countries, there is a huge paper work which takes a great time, lack of interaction between industry & academia, constraints for the Industry. Finally, the identified global issues are; removal of quota, awareness about the trade liberalization, worse image of Pakistan internationally, restriction of EU to buy raw material from them, lack of ETP, evaluation of factory, delay in delivery, lack of diversification in the direction of trade, Only developing country to sign the ILO conventions completely, millions of dollars spent to destroy Pakistans image internationally, quality issues, labor-intensive production, Increase in the foreign buyers check, Imposition of antidumping duties, preferential treatment to the competitors, competitors are much stronger.